Parasites in histopathology: A tertiary care hospital experience - Dr. Poovizhi Inbasekaran; Dr. Megala Chandrasekar; Dr. Thamilselvi Ramachandran; Dr. Anbu Lenin Kulandaivel (Tropical Journal of Pathology and Microbiology, 2021)
Background: Parasitic infections are a major public health problem worldwide with one quarter of world’s population is suffering from it. Intestinal and extraintestinal parasitic infestation are raising in developing countries. There is raise in immunocompromised state in which tissue parasitic infestation are increasing which necessitates this type of study. Method: A retrospective descriptive study with data collected from histopathology register from January 2018 to December 2020, all cases diagnosed as parasitic infestation with age, gender , location and histopathological evaluation with tissue response was analysed. Results: Over the period of 3 years 11 parasitic infestation was identified. 3(27.3%) cases of hydatid cyst, 5(45.5%) cases of Enterobius vermicularis, 2 (18.2%)case of cysticercosis and 1(9%) case of hard tick was identified. Most common age group affected was <25 years of age(54.5%). Most common parasite found is enterobius vermicularis in our study. Conclusion: A careful histopathological examination to identify parasitic infestations in tissue sections will help to decrease morbidity and mortality by providing specific treatment to the patient.